Ardu-electrochromic film for home safety and privacy purpose / Anas Akasyah Abd Patas ... [et al.] - Abd Patas, Anas Akasyah; Mohd Taib, Nur Athirah; Suhaimi, Syahida (2021)
The demands for smart devices are increasing exponentially nowadays. This project presents the invention of a new, low cost, and user-controlled electrochromic film device for home safety and privacy purposes. The development of this system focuses on windows where electrochromism materials as a film had been layered for the safety and privacy plan. The film material was chosen instead of mirror due to its cost effectiveness, convenient properties which are more versatile, and installable to any pre-existing glass available. The excessive exposure of UV radiation over 15 minutes causes acute and chronic long-term skin effects. Meanwhile, high cost in cutting precise glass appliances due to high volume of heat trapped during daylight causes the application of this device to be crucial. This invention is equipped with IoT (Internet of Things) which helps users to control it remotely via Blynk Apps in smartphones and displaying all the sensor’s output. The system comprises Arduino UNO as main controller, NodeMCU ESP8266 for IoT platform, solar battery as a power source, UV sensor together with PIR sensor to enhance safety purpose and DHT11 for monitoring temperature and humidity. The efficiency of the system was evaluated by measuring the changes in solar radiation and temperature in between inside/outside of the system. This simple, reliable, and economically smart Ardu-electrochromic film system is a new potential management device preventing excessive UV lighting in houses, promising privacy and safety as well.